(untitled) (Journal of Scientific Research, 2022)
The presence of microglial cells as resident macrophage population in the Central Nervous System (CNS) is well documented from the study of repairing of lesions in CNS that varies widely throughout the animal kingdom. The existence of neuroglia cells similar to vertebrate microglia and small mobile phagocytes and hemocytes were documented from ganglia of some invertebrate animal models like leech (H. medicinalis), insects (P. americana and D. melanogaster) and mollusca (M. edulis). Neuronal replacement and migration of immunocompetent cells (macrophage, microglia, ependymal cells etc.) after surgical lesions in CNS of non-mammals (fishes, reptiles and aves) are much restricted to specific neurogenic niches associated to the neural regeneration and migration of cells in invertebrates. Microglial presence is largely restricted in the optic tract of fish and amphibian ganglionic cells because they have a surprising capacity to regenerate their neurons after lesions. Hence the CNS of both invertebrates and vertebrates contain microglia like mononuclear phagocytes, ensheathing glia and reticular glia, which indicate about the evolutionary conserved innate immune response to maintain CNS development and health. But the presence and gradual changes in the structure and function of microglia and neuron-microglia relationship in the CNS along the phylogeny need to be focused thoroughly.